2012
DOI: 10.1371/journal.pone.0032243
|View full text |Cite
|
Sign up to set email alerts
|

The Mice Drawer System (MDS) Experiment and the Space Endurance Record-Breaking Mice

Abstract: The Italian Space Agency, in line with its scientific strategies and the National Utilization Plan for the International Space Station (ISS), contracted Thales Alenia Space Italia to design and build a spaceflight payload for rodent research on ISS: the Mice Drawer System (MDS). The payload, to be integrated inside the Space Shuttle middeck during transportation and inside the Express Rack in the ISS during experiment execution, was designed to function autonomously for more than 3 months and to involve crew o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 25 publications
1
55
0
Order By: Relevance
“…Decreased bone density and bone mass are issues associated with space flight [8]. The PTN-Tg mouse model was selected for the leading study in the MDS mission flown aboard the ISS, in order to determine whether PTN over-expression would provide protection from bone loss due to microgravity [8], [11]. The aim of present study was to examine effects of long-term space flight on immune parameters and the gut microbiota, through participation in a tissue-sharing program [11].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased bone density and bone mass are issues associated with space flight [8]. The PTN-Tg mouse model was selected for the leading study in the MDS mission flown aboard the ISS, in order to determine whether PTN over-expression would provide protection from bone loss due to microgravity [8], [11]. The aim of present study was to examine effects of long-term space flight on immune parameters and the gut microbiota, through participation in a tissue-sharing program [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nutelings et al . suggested that three months of exposure to space conditions induced skin atrophy and deregulated hair growth in mice that were maintained in the Mice Drawer System (MDS)60 for 91 days aboard the ISS61. Another recent study conducted in space during the STS-135 mission, where female C57BL/6 mice survived for 13 days, resulted in increased oxidative stress in the skin, which was assessed by examining 4-hydroxynonenal (4-HNE)62.…”
Section: Discussionmentioning
confidence: 99%
“…Several notable behavioral activities have been observed during space experiments, including floating, hanging, and holding on to the cage bars (Cancedda et al, 2012). The mice adapted quickly to microgravity locomotion by using their paws and tails to grasp the cage's grid walls.…”
Section: Introductionmentioning
confidence: 99%
“…Besides motion based behaviors, the mice interacted readily with additional stimuli, if present. The incorporation of stimuli and other pieces of environmental enrichment could greatly influence the wellbeing of these test rodents in space (Cancedda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%